Implementation of JSON Web Token based on the SHA-512 Algorithm for Authentication on BatikKita Applications - Andi Setiawan; Ade Irma Purnamasari (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Batikkita is an android based application and web framework laravel web service architecture that is used to bring together between craftsmen and consumers of batik Trusmi and batikkita application with the e-commerce model used is business to customer. The backend system interface used is a web framework while the frontend system interface used is android. The problem that arises from the Batikkita application is that the security of users, both as sellers and consumers, is very vulnerable to being hacked, so it is very detrimental to both sellers and buyers. This study aims to implement the JSON Web Token based on the HMAC SHA-512 algorithm in the Batikkita application in order to provide a sense of security for both the seller and the buyer before entering the sales transaction page. The application development method used is Rapid Application Development because the cycle used to develop our batik application is very short so it is very helpful in this research. While the implementation of JSON Web Token with the HMAC SHA-512 algorithm in the Batikkita application is used to improve user security when logging in to the Batikkita application in the form of a token and the password used by the user is wrapped in a token given by the Batikkita application. As a comparison, the HMAC SHA-256 algorithm and the HMAC SHA-384 algorithm are used. The results obtained from testing the implementation of JSON Web Token with the SHA-512 algorithm in our batik application, for an average increase of speed between 138.8 milliseconds for SOAP and 122.7 milliseconds for REST compared to the HMAC SHA-256 algorithm and the HMAC SHA-algorithm. 384. While the required token size is greater between 2.13 kb for SOAP and 2.11 kb for REST compared to the HMAC SHA-256 algorithm and the HMAC SHA-384 algorithm.